A função social do contrato como princípio de preservação e desenvolvimento econômico e organismo de limitação da autonomia da vontade e a onerosidade excessiva - Generoso, Fábio Augusto (2008)
The contract, after all, is a link that, of a side, puts the value of the individual as that one that creates it, but, of another side, it establishes the society as the place where the contract goes to be executed and where it goes to receive a reason from balance and measure (Reale, 1986). This the new contract conception. For such reasons, it is that the possibility of the judicial revision of contractual the legal transaction has been admitted modernly, substituting it volitional declaration of the contractors for the state will, with sights to the business balance and its feasibility.